Size-Dependent Effects of Suspended Graphene Oxide Nanoparticles on the Cellular Fate of Mouse Neural Stem Cells - Lin L (Dove Medical Press, 2020)
Lijuan Lin,1,2,* Xizhen Zhuang,1,2,* Ruiqi Huang,1 Simin Song,1 Zhaojie Wang,1,2 Shilong Wang,3 Liming Cheng,1,2 Rongrong Zhu1,2 1Division of Spine, Department of Orthopedics, Tongji Hospital Affiliated to Tongji University School of Medicine, School of Life Science and Technology, Tongji University, Shanghai, People’s Republic of China; 2Key Laboratory of Spine and Spinal Cord Injury Repair and Regeneration (Tongji University), Ministry of Education, Shanghai, People’s Republic of China; 3Research Center for Translational Medicine at East Hospital, School of Life Science and Technology, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rongrong Zhu; Liming ChengDivision of Spine, Department of Orthopedics, Tongji Hospital Affiliated to Tongji University School of Medicine, School of Life Science and Technology, Tongji University, Shanghai 200065, People’s Republic of ChinaTel +86 21 66111330Email rrzhu@tongji.edu.cn; limingcheng@tongji.edu.cnPurpose: In this study, we aim to explore the effects of graphene oxide (GO), a derivative of graphene, nanoparticles of four different sizes on the cellular fate of mouse neural stem cells (mNSCs).Methods: GO NPs were characterized with transmission electron microscopy (TEM), scanning electron micrography (SEM), atomic force microscopy (AFM) and Raman Spectra analysis. The cytotoxic effects of the GO NPs of different sizes on the mNSCs were determined using CCK-8 assay, Annexin V-APC/ 7-AAD staining and EdU staining assays. We investigated the biological and the mechanisms of GO NPs on cells using immunofluorescence analysis and quantitative real-time PCR (qPCR).Results: The average hydrodynamic sizes of the GO NPs were 417 nm, 663 nm, 1047 nm, and 4651 nm, with a thickness of approximately 22.5 nm, 17.7 nm, 22.4 nm, and 13.4 nm, respectively. GO NPs of all sizes showed low cytotoxicity at a concentration of 20 μg/mL on the mNSCs. Immunostaining demonstrated that treatment with GO NPs, especially the 663 nm ones, enhanced the self-renewal ability of mNSCs in the absence of EGF and bFGF. Under differentiation medium conditions that are free of mitogenic factors, all the GO NPs, particularly the 4651 nm ones, increased the expression level of Tuj1 and GFAP. With regards to the migration ability, we found that 417 nm GO-NP-treated mNSCs migrated over a longer distance than the control group obviously. In addition, higher expression of Rap1, Vinculin and Paxillin was observed in the GO NP-treated groups compared to the control group. mRNA-Sequence analysis and Western blotting results suggested that the 4651 nm GO NPs triggered positive neuronal differentiation through phosphorylation of ERK1/2 by the downregulating of TRPC2.Conclusion: GO NPs play an important role in the applications of inducing self-renewal and differentiation of mNSC, and are promising in the future for further studies.Keywords: graphene oxide, neural stem cells, size-dependent, self-renewal, differentiation